Lecturers’ Digital Readiness in the Context of Digital Scholarchy - Suwendi, Suwendi; Mesraini, Mesraini; Bakti Gama, Cipta; Rahman, Hadi; Luhuringbudi, Teguh; Sangsawang, Thosporn (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study focuses on the digital readiness of lecturers at Islamic Religious Colleges (PTKI) in Jakarta and Banten in the context of Digital Scholarchy. The purpose of the study is twofold: firstly, to explore the attitudes and knowledge of lecturers regarding the use of digital technology, and secondly, to identify the digital literacy gaps among them. The data collection method uses questionnaires, interviews, and documentation to provide a more rigid and focused picture. The data analysis utilizes a range of approaches, including the Digital Readiness and Attitude Framework, the Technology Acceptance Model, and the Digital Literacy Framework, to uncover factors that influence the digital readiness of lecturers. The study's findings indicate that although there are positive attitudes towards technology, its understanding and practical use are still limited, resulting in a digital divide within the academic environment. The study's conclusions provide scientific contributions in the form of new understandings of the interplay between technology, culture, and psychology in the context of higher education by suggesting further research to explore the impact of socialization programs, training, and mentoring in the future. This study is the basis for formulating policies that are more adaptive and responsive to the needs of lecturers at PTKI Jakarta and Banten in this digital and disruptive era. The implications of this research highlight the need to develop training and mentoring programs to improve the digital skills of lecturers at PTKI Jakarta and Banten. These findings can also help build more adaptive policies and support changes in higher education in the digital era.